ANALISIS PERSEBARAN ZONA RESERVOIR LAPANGAN DT-1 MENGGUNAKAN METODE INVERSI IMPEDANSI AKUSTIK DAN ATRIBUT VARIANSI - Tyas Vicri Hijria; Hernowo Danusaputro (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Has analyzed the distribution of reservoir zone at DT-1 field using accoustic impedance inversion and attribute of variance was performed to analyze the reservoir zone based on the porosity values and the attribute variance values at DT-1 field. Porosity values obtained from acoustic impedance inversion are transformed into the porosity value by leveraging relationships porosity and acoustic impedance values are inversely proportional. While the value of variance will provide information discontinuity seismic trace where this indicates a fault, stocky, and others to support the prospect reservoir zone. From this research showed that the porosity value and the value of variance in the bottom zone of the well DT-1 proved enough lies depth in the tight layer below the reservoir zone wells DT-1. In addition to the time between Mantawa horizon (target formation) with Base horizon showed good results in demonstrating the value of variance and porosity values of mutual support prospects zone of finding a new reservoir that is the northern region stretches eastward field DT-1. Zone prospect obtained reservoir porosity of 20% - 25% with variance value above 0.1 and acoustic impedance values 24000-28000 ((ft / s) * (g / cc)).